Enhanced-charge transfer over molecularly imprinted polyaniline modified graphene/TiO2 nanocomposite electrode for highly selective detection of fipronil insecticide. (15th November 2022) - Nurdin, Muhammad; Arham, Zul; Irna, Wa Ode; Maulidiyah, Maulidiyah; Kurniawan, Kurniawan; Salim, La Ode Agus; Irwan, Irwan; Umar, Akrajas Ali
Abstract: Fipronil contamination in agricultural products and livestock has become a growing concern because its long-term exposure to its toxicity effect on humans may cause the failure of organs, like kidney and liver, and neurological disorders. Early detection of this substance's presence in agricultural and livestock products should be established to minimize its fatal effect. Here, we demonstrate a fabrication of high sensing sensitivity and selectivity electrode for electrochemical detection of fipronil pesticide, i.e. molecularly imprinted polyaniline modified graphene/TiO2 nanocomposite (Gr/TiO2 @MIP-PANi). The results show that the composite electrode is extremely sensitive to the fipronil by showing a highly active electron transfer with an oxidation potential as low as 0.21 V. The sensing sensitivity of the composite electrode also exhibits excellent linearity to the fipronil concentration within a range of 1.0 mM–8.0 mM. This gives the limit of detection (LoD) value as low as 0.74 mM. Our analysis also showed that the existence of facile diffusion of fipronil onto the composite electrode is the key factor for the high sensing sensitivity of the composite electrode. In addition, the composite electrode also demonstrate a high selectivity properties as it can detect the presence of 5 mM fipronil in the 5 mM profenofos interference compound. These results signify that the new Gr/TiO2 @MIP-PANi nanocomposite electrode should find extensively used for sensitive and selective detection of fipronil in food products. Graphical abstract: Molecularly imprinted polyaniline modified graphene/TiO2 ncomposite electrode promotes an active electron transfer with fipronil pesticide for highly sensitive fipronil detection. Image 1 Highlights: Synthesis of molecularly imprinted polyaniline modified graphene/TiO2 nanocomposite electrode is presented. The composite electrode provides an active electron transfer with fipronil pesticide for a high sensing sensitivity. The electrode exhibits excellent selectivity to fipronil detection.